Moving towards a Normalised Path: Political Islam in Contemporary Indonesia - RIDHO AL-HAMDI (Universitas Muhammadiyah Yogyakarta, 2017)
As the largest predominantly Muslim country of the globe, Indonesia nearly achieves two decades of its democratisation wave since the downfall of the Au- thoritarian Rule in 1998. Political parties, one of the crucial democratic institutions, have a signifi- cant responsibility to maintain the democratic system as they are the sole official representatives to create leaders and policies in the government. This paper portrays the trajectory of political Islam in Indonesia particularly Islam-based parties slightly under two decades since Post- New Order regime. Islam-based parties have a potential to be a moderate-offi- cial force in the government. It could be proven by the threefold indicator. First is the ripeness of Islam-based parties in coping with both internal and external stimuli such as the leadership change and elite conflicts, the constitutional re- form and the electoral result. Second is the role of Muslim political forces in the parliament particularly in addressing the policy making of controversial bills. Third is the involvement of Islam-based parties in the administration cabinet. To sum up, by applying the analytical framework on the party goal, political Islam in Indonesia has three distinctive features: As “the vote-seekers” in the election, as “the issue-advocates” in the legislature and as “the office-seekers” in the execu- tive. These denote to a normalised path of political Islam in reaching out the embedded democracy.